6*6x=89x*1

Simple and best practice solution for 6*6x=89x*1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6*6x=89x*1 equation:


Simplifying
6 * 6x = 89x * 1

Multiply 6 * 6
36x = 89x * 1

Reorder the terms for easier multiplication:
36x = 89 * 1x

Multiply 89 * 1
36x = 89x

Solving
36x = 89x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-89x' to each side of the equation.
36x + -89x = 89x + -89x

Combine like terms: 36x + -89x = -53x
-53x = 89x + -89x

Combine like terms: 89x + -89x = 0
-53x = 0

Divide each side by '-53'.
x = 0

Simplifying
x = 0

See similar equations:

| -9d+7-6d=-133 | | 2b^2+4b+2=0 | | 3x+2-x=6+5x-3 | | m-1/3=-9 | | 2*5x=5x*6 | | 6x+6+7x+5=115 | | 3*x=7*1x | | 6x+6+8x+7=69 | | -2=-49x(2)-7x | | 4a^2-147=0 | | -2g^2-6g+14x^2/(g+5) | | 4x+4+2x+9=31 | | -2g^2-6g+14x^2/g+5 | | 12x+16=3x+9 | | 28x^5-36x^4+8x^3= | | 7x*6=34x*6 | | 5x+2+2x+3=47 | | X/7+10=9 | | 1/2n+10=20 | | 2x-9=-33-4x | | 34x*6=7x*6 | | 2x+0.625=3x-0.625 | | X/3+5=-1 | | 3x-6=-1 | | 6x*6=7*4x | | 3x*5=7x*6 | | f(x)=4x^3+5x^2-6x-4 | | -15b^2+102b+21= | | 35=-4+5(a+3) | | 3a+2b+3c=10000 | | 4*5x=4*4x | | y-8=-4/9(18) |

Equations solver categories